The Social Wage, Welfare Policy, and the Phases of Capital Accumulation - Jamee K. Moudud; Ajit Zacharias (Levy Economics Institute of Bard College, 1999)
This paper addresses two broad questions. The first one relates to the economic rationale for the existence of the welfare state. To address this question, we review the marginalist arguments and then counterpose a historical and institutional analysis of the rise of the U.S. welfare state. The second question concerns the macroeconomic impacts of welfare spending. We examine the standard neoclassical macroeconomic arguments for and against welfare cutbacks and then propose an alternative growth framework, rooted in the classical and Harrodian traditions, to evaluate social policy. We argue that the alternative framework provides both demand-side and supply-side mechanisms whereby social spending can be supported without harmful long-run macroeconomic effects. Our analysis suggests that, in general, because growth and crises are endogenous, there may be no tension between social policy and economic performance. Specifically, the recent cutbacks in the U.S. are hard to justify on purely economic grounds.
Keywords: 330